Lexical Word-Class Distributions in Research Articles of Four Subject Areas - Kwary, Deny A; Artha, Almira F; Amalia, Yuni S (Kalbų Studijos, 2018)
This study aimed to determine the lexical word-class distribution in research articles of four subject areas: social sciences, health sciences, physical sciences and life sciences. A total of 5,754,560 tokens or running words were extracted from research articles published by Elsevier for examination. Results show both similarities and differences in distribution across the four subject areas. For health, physical and life sciences, the noun is the most dominant lexical word class, followed by the adjective, verb and adverb. For social sciences, the verb is more dominant than the adjective. This finding reflects that research articles in social sciences use the highest number of words and are more conversational in nature. For types of nouns, singular nouns are used more often than plural nouns in all subject areas; this usage might indicate that research articles tend to focus on a single research object. For types of verbs, research articles in health, life and physical sciences tend to prefer using past tense and past participle forms over others; this usage indicates emphasis on reporting what has been done. In contrast, social sciences research articles show more frequent use of the verbs’ base form, and this usage possibly signifies arguments regarding general truths.